Analysis and risk assessment of pharmaceutical residues in fish from three water bodies in Ghana - Albert Ebo Duncan; Christian Adokoh; Martha Osei-Marfo; Samuel Barnie; Aboagye George Sakyi; Josephe Adjei (Journal of Water and Health, 2023)
Illegal mining has overshadowed pharmaceutical pollution even though exposure to pharmaceutical waste is high. Consumption of fish potentially polluted with pharmaceuticals from the rivers continues with little concern or potential threat it poses. In the present study, the residues of one antibiotic (Chloramphenicol), five hormones (progesterone, 17-beta Estradiol, Estrone, 17a-Ethynylestradiol, and one), three environmental contaminants (4-para-nonylphenol, 4-tert-octylphenol, and Bisphenol A), one barbiturate (Primidone) and one analgesic (Diclofenac sodium salt), were investigated from fish samples from the rivers Pra, Narkwa, and the Volta. The results show a high concentration of drugs in River Pra in comparison to those in Rivers Narkwa and Volta. The hazard quotients (HQs) for the environmental contaminants were all above 1, except Bisphenol A. Furthermore, the HQs from this study suggest that consumers of fish from any of the three rivers stand a hazard risk of Chloramphenicol (19), 17a-Ethynylestradiol (4), Estrone (1.366), Diclofenac sodium salt (3.29), Progesterone (4.598), 4-tert-octylphenol (87.2), and 4-para-nonylphenol (7.252), but negligible risk against E2 (0.687), Primidone (0.014), Testosterone (0.16), and Bisphenol A (0.642). Of the fish species studied, the highest concentration of all pharmaceuticals put together is found in Clarias gariepinus, Labeo senegalensis, and Chrysichthys nigrodigitatus in that order. HIGHLIGHTS There is a high potential for pollution of pharmaceuticals.; River Pra is most polluted with pharmaceuticals.; Clarias gariepinus is the most polluted fish species.; The hazard quotients for the environmental contaminants were all above 1, except Bisphenol A.; The hazard quotients from this study suggest that consumers of fish from any of the three rivers stand a potential hazard risk.;